2018
DOI: 10.29252/nfsr.5.2.47
|View full text |Cite
|
Sign up to set email alerts
|

Is Trans Fatty Acid Still an Issue for Policy Makers in Iran? A Technical Report

Abstract: A B S T R A C TIn recent decades, the oil industry has changed its direction toward vegetable oil use instead of animal fats due to various reasons such as a small numbers of animal fat resources and high saturated fatty acids content in animal fats. Therefore, different modification processes have been used to alter the physicochemical properties of vegetable oils, which lack functionality and oxidative stability in their native form. Hydrogenation process is a common way to produce plastic fats with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
(21 reference statements)
0
12
2
Order By: Relevance
“…The results of Nour et al study in Egypt on hydrogenated vegetable oil are somewhat different from the results of our study that is due to the fact that Egyptian hydrogenated vegetable oil is made from palm oil while Iranian hydrogenated vegetable oil is made from a mixture of soybean oil, canola, corn, etc [5,13,16]. As we know, palm oil is source of atherogenic fatty acids naturally.…”
Section: Hydrogenated or Partial Hydrogenated Oilcontrasting
confidence: 91%
See 3 more Smart Citations
“…The results of Nour et al study in Egypt on hydrogenated vegetable oil are somewhat different from the results of our study that is due to the fact that Egyptian hydrogenated vegetable oil is made from palm oil while Iranian hydrogenated vegetable oil is made from a mixture of soybean oil, canola, corn, etc [5,13,16]. As we know, palm oil is source of atherogenic fatty acids naturally.…”
Section: Hydrogenated or Partial Hydrogenated Oilcontrasting
confidence: 91%
“…In contrast with our nding, the results of a randomized clinical trial on 206 Iranian adults are shown that margarine consumption has decreased the amount of AIP slightly. According to Iranian standards 5 types of margarine are produced with different amounts of Trans fatty acids [13], Perhaps the difference of results is related to the type of consumed margarine in the two studies.…”
Section: Margarinementioning
confidence: 96%
See 2 more Smart Citations
“…In terms of regulations, the national standards for salt, sugar, and fat in processed food were revised as follows: salt intake to be reduced from 2.3 to 1%, while sugar and carbonate in industrial juices to be reduced to less than 10%. The SCHFS approved a reduction of palm oil import by 30% as well as the use of trans fatty acids in the confectionery and chocolate industry to less than 10% [58][59][60][61]. More than 1400 nutrition counselors were hired within PHC centers.…”
Section: Discussionmentioning
confidence: 99%